PROGRAM PENDAMPINGAN PEREMPUAN BAGI PEGIAT INDUSTRI RUMAHAN - Muhammad Kamaluddin (SOSFILKOM : Jurnal Sosial, Filsafat dan Komunikasi, 2018)
There are times when women become the economic support of their families. Primarily infinancial matters, their dependence on men has the potential to be counterproductive to thespirit of equality. This paper is a study of the Mentoring Program for Women KPPPA-RIHome Industry Activists in Cirebon Regency. Through questionnaire-based mapping, 100women entrepreneurs from two villages (Grogol and Mertasinga) in GunungjatiSubdistrict were categorized according to the business sectors they engaged in. Importantaspects such as capital, labor, raw materials, tools, packaging, selling prices, marketingand bookkeeping have become the focus of attention.Keywords: Home Industry, Women, Mentoring Program